Exposure of Monocytic Cells to Lipopolysaccharide Induces Coordinated Endotoxin Tolerance, Mitochondrial Biogenesis, Mitophagy, and Antioxidant Defenses - Widdrington, John D.; Gomez-Duran, Aurora; Pyle, Angela; Ruchaud-Sparagano, Marie-Helene; Scott, Jonathan; Baudouin, Simon V.; Rostron, Anthony J.; Lovat, Penny E.; Chinnery, Patrick F.; Simpson, A. John (Frontiers in Immunology, 2018)
In order to limit the adverse effects of excessive inflammation, anti-inflammatory responses are stimulated at an early stage of an infection, but during sepsis these can lead to deactivation of immune cells including monocytes. In addition, there is emerging evidence that the up-regulation of mitochondrial quality control mechanisms, including mitochondrial biogenesis and mitophagy, is important during the recovery from sepsis and inflammation. We aimed to describe the relationship between the compensatory immune and mitochondrial responses that are triggered following exposure to an inflammatory stimulus in human monocytic cells. Incubation with lipopolysaccharide resulted in a reversible change in the immune phenotype of THP-1 cells consistent with the induction of endotoxin tolerance, similar to that seen in deactivated septic monocytes. After exposure to LPS there was also early evidence of oxidative stress, which resolved in association with the induction of antioxidant defences and the stimulation of mitochondrial degradation through mitophagy. This was compensated by a parallel up-regulation of mitochondrial biogenesis that resulted in an overall increase in mitochondrial respiratory activity. These observations improve our understanding of the normal homeostatic responses that limit the adverse cellular effects of unregulated inflammation, and which may become ineffective when an infection causes sepsis.